Sun exposure and Vitamin D in rural India: A cross-sectional study - Shobhit Garg; Aparajita Dasgupta; Swanya Prabha Maharana; Bobby Paul; Lina Bandyopadhyay; Aritra Bhattacharya (Wolters Kluwer Medknow Publications, 2018)
Background: Vitamin D deficiency/Vitamin D Insufficiency (VDI) is now recognized as a pandemic. Cutaneous exposure to ultraviolet-B causes photolysis of epidermal 7-dehydrocholesterol, converting it to pre-Vitamin D3 (precholecalciferol), which then undergoes isomerization to form the stable hormone Vitamin D3. Objectives: The objectives of the study is to determine the status of Vitamin D level among the adults residing in a rural area of West Bengal and to find out the optimal cutoff of the sun exposure for Vitamin D sufficiency. Methods: This study was a rural community based cross-sectional study. It was done from May 2016 to April 2017 among 197 adults residing in a rural block of West Bengal. Data were collected by interviewing the respondents with the help of a structured pre-tested pre-designed schedule. After interviewing, every individual was examined for height and weight and blood was collected for serum Vitamin 25-(OH) D. Receiver Operating Characteristic (ROC) curves were utilized to find out optimum cut-off for sun exposure using Youden's index. Binary logistic regression was performed to find out the associates of high sun exposure. All analysis was done using R. Results: Overall VDI was found in 133 (67.5%). Among them, 102 (51.8%) were female. On ROC curve for veritable sun exposure for Vitamin D sufficiency, area under curve was 0.7841 which signifies veritable sun exposure as a good screening tool. Conclusion: Proper information, education, and communication material regarding various aspects of sun exposure and Vitamin D should be prepared with due consultation of field experts and disseminated to increase awareness among the community.